METAPHYSICAL THINKING: THE RELEVANCE OF THE PROBLEM - Sukhodub , Tetiana (Proceedings of the National Aviation University Series Philosophy Cultural, 2025)
The article examines the characteristics of metaphysical thinking in the context of its comparison with post-metaphysical approaches in contemporary philosophy. The aim of the study is to analyze the characteristics and interrelation of metaphysics and post-metaphysics as essential directions of universal philosophical thinking. Research methodology includes a scientific and systemic approach, cognitive premises of the hermeneutics of being, which interprets understanding as the meaning of human experience, and the historical method. Research results. Post-metaphysical thinking, as a prevalent concept in contemporary philosophical discourse, does not replace metaphysics but rather expands its subject matter and the boundaries of metaphysical thinking. The posing of questions regarding the ultimate “beginnings” of being characterizes contemporary philosophy of science and thereby actualizes metaphysical thinking at a new stage of cognition. Discussion. An analysis of the works of M. Dummett, E. Coreth, M. Lax, M. Margaroni, L. Oblova, S. Sinyakov, J. Habermas, M. Heidegger, Yu. Kharchenko, and others made it possible to reveal key aspects of the formation of metaphysical thinking in the history of philosophy, and to distinguish the problems of ontology and metaphysics, as well as metaphysics and post-metaphysics. Conclusions. Metaphysical thinking is a person’s reflection on the knowledge of being achieved in a particular era. The focus of metaphysics on universality and thinking about the world as a whole, presupposes a categorical understanding and clarification of the logical and socio-cultural content of the categories "universal," "whole," "existent," "substance," "matter," "consciousness," "being,” “meaning,” and others. In contemporary scientific discourse-philosophical, socio-humanitarian, and natural sciences – the culture of metaphysical thinking serves as a “mediated subject” in the scientific search for the universal foundations of human existence. Keywords: being, ontology, metaphysics, post-metaphysics, philosophical thinking, categories, understanding